ANALISIS SPASIAL SEBARAN TINGKAT KEKRITISAN LAHAN DI SUB DAS BIYONGA KABUPATEN GORONTALO - Sri Rahayu Ayuba (Universitas Tamansiswa Padang, 2022)
This research was conducted in the Biyonga Sub-watershed of Gorontalo Regency. The purpose of this research is to look spatially at the level of land criticality in the Biyonga Sub-watershed and see the effect of the effective depth of the soil. This study uses scoring and overlay methods with the help of Geographic Information Systems. The results showed that the Biyonga Sub-watershed has four land criteria including Critical Potential with an area of ??170.7 Ha, Somewhat Critical 4048 Ha, Critical 2396 Ha and Very Critical 2300.4 Ha which influence on the effective depth of the land based on field measurements marked on the land very critical and critical with the condition of the effective depth of relatively shallow soils that is between 60-30 cm.